Raising the future together: Assessing the impact of the Chics program on primary caregivers in low-income daycares - Antoinette van der Merwe; Catherine Senyolo; Attie van Niekerk (Sustainable Futures)
Parental involvement in a child's school is crucial during early childhood, a critical period for skill-forming and neurodevelopment. However, the impact of early childhood programs on parents is understudied. This study evaluates the Chics program – which includes teacher training, an improved curriculum, and support meetings – on parental involvement in low-income daycares in South Africa, focusing on parents’ wellbeing, unity, knowledge, and agency. Focus groups and surveys with 126 parents showed the program had positive changes in parental unity, life satisfaction, and agency, encouraging community projects. The results could advice other programs to cost-effectively increase parental involvement in daycare centres.